Lessing's "Aesthetica in Nuce" An Analysis of the May 26, 1769, Letter to Nicolai - Anthony Rudowski, Victor (UNC Studies in the Germanic Languages and Literatures, 1971)
This letter contains Lessing's most explicit observations on the distinction between poetry and prose as well as a unique proposal for emending Aristotle's interpretation of the dramatic method. Although both arguments are formulated in terms of Abbé Dubos' theory of signs, Lessing significantly modifies Dubos' doctrine by ideas derived from Alexander Baumgarten, Moses Mendelssohn, and Edmund Burke. An analysis of these modifications provides the framework for a critique of Lessing's aesthetic philosophy as a whole.